MODEL KONSEPTUAL SISTEM REWARD DAN PUNISHMENT UNTUK MENINGKATKAN KINERJA GURU DI MTS AR-RAHMAH BOGOR: STUDI RANCANG BANGUN MODEL BERBASIS DATA LAPANGAN - Wahyudin, Didin; Kurniawan, Imam; Rusmiati Aliyyah, Rusi; Milenia Vebrianti, Mega; Palah (At-Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to design a conceptual model of a reward and punishment system based on field data as a reference to improve teacher performance at MTs Ar-Rahmah Bogor. The research employed a qualitative exploratory approach, using observation, in-depth interviews, and documentation as data collection techniques. The findings reveal that the implementation of reward and punishment at MTs Ar-Rahmah is still informal, incidental, and lacks structured performance indicators or written procedures. Rewards are given symbolically without clear evaluation criteria, while punishment s are limited to verbal warnings without standard operating procedures or structured coaching programs. Based on a SWOT analysis, the researchers formulated a conceptual model consisting of five key components: teacher performance indicators, regular evaluations, forms of reward, stages of punishment , and documentation and SOPs. This model is expected to serve as a reference for developing a more structured and sustainable teacher performance management system. The study recommends a limited-scale pilot implementation, involving teachers in the formulation of indicators and evaluations, and conducting regular adaptive monitoring.